Employee Service Communication in Creating Customer Satisfaction at Cue Club Pool and Coffee - Fajar Arifin Wijanarko; Nunik Hariyani; Zulin Nurchayati (CV Edujavare Publishing, 2026)
This study examines how frontline employees' service communication shapes customer satisfaction in a business that combines two simultaneous service lines billiard and café using Cue Club Pool and Coffee in Madiun, Indonesia, as a case. Prior qualitative accounts of interpersonal service communication have concentrated on single-line service settings such as hotels, restaurants, banks, and hospitals, and the limited work on billiard-café ventures has examined servicescape and experiential marketing without addressing how frontline communication itself is enacted or how it translates into satisfaction. This study addresses that gap. Using a qualitative case study design, data were collected from five purposively selected informants (three customers and two employees) through semi-structured interviews, participant observation, and documentation, and analyzed with Miles, Huberman, and Saldaña's interactive model through open, axial, and selective coding. Findings show that employees' service communication reflects DeVito's five interpersonal characteristics (openness, empathy, supportiveness, positiveness, equality) with uneven consistency, and as this study's central contribution that customer satisfaction is generated through two distinct mechanisms: a functional pathway (speed, information reliability, transactional accuracy) and a relational pathway (personal familiarity, preference recognition, memorable service moments), with the relational pathway emerging as the stronger driver of satisfaction that exceeds expectations. Declines in the SERVQUAL dimensions of reliability and responsiveness are explained by workload pressure and the emotional labor employees perform to sustain positive affect during high-traffic periods. The study contributes a dual-pathway model of satisfaction formation in combined entertainment-service businesses and offers practical recommendations for similar ventures